2020
DOI: 10.3928/00989134-20191118-01
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effect of a Home Health Heart Failure Intervention on Hospital Readmissions, Heart Failure Knowledge, Self-Care, and Quality of Life

Abstract: For older adults, heart failure (HF) has the highest 30-day hospital readmission rate of any chronic illness. Despite research into strategies to reduce readmissions, no single program has emerged as sustainable. The purpose of the current study was to test a researcher-developed home health nurse HF intervention (CareNavRN ™ ) on 30-day readmission rates, HF knowledge, self-care, and quality of life (QOL) among 40 older adults transitioning home. Home health nurses received specialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…The studies were conducted in Australia ( n = 2), China ( n = 6), Singapore ( n = 2), USA ( n = 7), South Korea ( n = 1), Turkey ( n = 1), Germany ( n = 1), Sweden ( n = 2), Japan ( n = 1), Iran ( n = 1) and Jordan ( n = 1). The attrition rates ranged from 0% (Leavitt et al., 2020) to 44.4% (Chew et al., 2021). Two studies both reported two experimental groups (Jiang et al., 2021; Schmaderer et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were conducted in Australia ( n = 2), China ( n = 6), Singapore ( n = 2), USA ( n = 7), South Korea ( n = 1), Turkey ( n = 1), Germany ( n = 1), Sweden ( n = 2), Japan ( n = 1), Iran ( n = 1) and Jordan ( n = 1). The attrition rates ranged from 0% (Leavitt et al., 2020) to 44.4% (Chew et al., 2021). Two studies both reported two experimental groups (Jiang et al., 2021; Schmaderer et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…We were concerned that the randomization process of five trials was bias since these trials did not provide clear information on the strategies used to achieve randomization and/or allocation concealment (Clark et al, 2015;Otsu & Moriyama, 2011;Redeker et al, 2022;Saleh et al, 2022;Yu, Chair, et al, 2015); moreover, Redeker et al (2022) were reported to have a statistically significant difference in one key baseline characteristic between groups. Nine articles were considered to have some concerns of bias in terms of the deviations from the intended intervention domain due to the usage of improper analytic strategies or vague information on the analyses (İlaslan & Özer, 2021;Jiang et al, 2021;Leavitt et al, 2020;Otsu & Moriyama, 2011;Redeker et al, 2022;Sadeghi Akbari et al, 2019;Saleh et al, 2022;Wang et al, 2017;Yu, Chair, et al, 2015). We are also concerned about the risk in measurement of the outcome domain for all the studies as double blinding is impossible in these studies and thus may affect the subjective outcome assessment.…”
Section: Quality Appraisal Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most self-care intervention programs used to reduce re-hospitalization of HF patients tend to focus on increased knowledge of HF and its symptoms, treatments, and self-care, improved adherence to self-care behaviors (i.e., medical recommendations), or nurses' assessment of their signs and symptoms, (telephone follow-up, home care, messaging, and tele-monitoring) [ [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. Early after their discharge, patients tend to have difficulties identifying immediate physical effects caused by their behavior, and often do not even perceive changes during exacerbation until their health status worsens to the point that they have to be readmitted [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Educational programs tailored to empower patients with HF on self-care showed significant improvement in their knowledge and practice ( Awoke et al, 2019 ; Koirala et al, 2018 ; Leavitt et al, 2020 ). Nursing theory-guided educational programs have strongly emerged as an effective strategy to provide comprehensive care to clients.…”
Section: Literature Reviewmentioning
confidence: 99%